762 Myocardial bridge evaluation towards personalized medicine (the rialto registry): preliminary findings. (8th December 2021) - Ciliberti, Giuseppe; Casamassima, Fabio; Laborante, Renzo; Restivo, Attilio; Migliaro, Stefano; Libbi, Lucrezia; Mottola, Francesco; Canonico, Francesco; Crea, Filippo; D'Amario, Domenico
Abstract: Aims: Myocardial bridge (MB) is the most common inborn coronary artery variant in which a segment of an epicardial coronary artery takes a tunneled course under a bridge of myocardium. MB has been documented from 1.5% to 16% of invasive angiographic series thus the true prevalence of MB is uncertain. The clinical relevance of MB is heterogeneous, being usually an asymptomatic bystander. However, a growing body of evidence suggests its association with myocardial ischaemia. In the present work, by setting up a database of patients affected by MB, we sought to assess their clinical characteristics and risk of major adverse cardiac events (MACE). Methods and results: This is a prospective/retrospective study and observational study in which we included 17 681 patients referred to undergo invasive coronary angiography (ICA) for suspected coronary artery disease. During the screening phase, we found that 338 cases (26 non-recruitable) were reported to have MB (1.9%). In-hospital clinical-instrumental data was acquired after ICA. The data obtained in the follow-up (FUP) visit is also included in the study. In particular, we recorded MACE and Seattle Angina Questionnaire (SAQ). The most frequent location of MB was the LAD coronary artery (96.8%). Other locations were the circumflex artery (1.3%), the right coronary artery (1%), the posterior interventricular artery (0.6%), and the first diagonal artery (0.3%). Chronic coronary syndrome (CCS) was the most frequent clinical presentation (47.5%). A big proportion (34.6%) of our patients were found to have MB during the occurrence of an acute coronary syndrome (ACS). In acute setting, unstable angina was the most frequent clinical presentation (17.6%). 47 patients (15%) underwent coronary angiography with provocative test (intracoronary acetylcholine) in order to search vasomotor disorders: according to COVADIS criteria, 17 procedures (5.5%) resulted positive for vasospastic angina (VSA). Invasive functional assessment with FFR/iFR was accomplished to assess the haemodynamic significance both of MBs and atherosclerotic plaques proximal to the MB segment in 35 patients (11.2%): in nine procedures (2.9%), functional tests resulted positive. β-Blockers (BBs) are suggested as first-line drugs as they increase diastolic filling time, by decreasing heart rate. Calcium channel blockers (CCBs) are useful, in VSA setting, to reduce epicardial spasm. In our court, 40% of patients toke BBs and 20% of patients toke CCBs at admission. The primary endpoint of the study is the incidence of MACE, defined as the composite of cardiac death, myocardial infarction and cardiac hospitalization. Considering patients who have already undergone FUP (114; 36.5%), we recorded 19 MACE (16.7% of patients with FUP). The secondary endpoint is the rate of patients with SAQ Angina Summary Score < 70: the rate of patients with SAQ < 70 is 23.7% at 6 months, 23.8% at 12 months and 23.2% at 24 months. Conclusions: MB has been typically considered benign and asymptomatic, but its clinical relevance is still matter of debate. A remarkable proportion of our patients were found to have a MB during the occurrence of ACS or CCS, highlighting that different mechanisms of ischaemia may coexist. Furthermore, invasive functional assessment shows a plausible correlation between MB and vasomotor disorders. Our study is still ongoing, and we hope to maximize the data in order to have a solid comprehension of MB and to propose the assessment that may indicate a tailored therapy.